Resilience and academic performance in fifth and six primary school student - Gallesi G., Rossina (2012)
The aim of this study was to determine the relationship between personal factors of resilience and academic achievement. The sample consisted of 202 students from 5th. and 6th. Grade of primary education, both sexes, whose ages range between 9 and 14, who completed the Inventory of Personal Resilience Factors proposed by Salgado (2005) and academic performance was assessed through the qualifications in the subjects more significant and the average grades of the semester. The results showed a significant relationship between personal factors of resilience and academic achievement. It is found that: personal factors esteem and Empathy have significant correlation with all areas of academic achievement. Communication, Mathematical Logic and Personal Social. Humor with communication, Science, Environment and Social Personal with Creativity. Resilience has significant correlation with all areas of academic achievement. In Empathy, Creativity and Resilience significant differences were found for women. In Self-Esteem, Creativity and Resilience Autonomy significant differences were found for students in 5th. Degree. Women have a significantly higher academic achievement than boys in Communication, Science and Environment and social Personal.